"Everyone needs to understand each other's systems": Stakeholder views on the acceptability and viability of a Pharmacist Independent Prescriber role in care homes for older people in the UK. (2nd March 2020) - Lane, Kathleen; Bond, Christine; Wright, David; Alldred, David P.; Desborough, James; Holland, Richard; Hughes, Carmel; Poland, Fiona
Abstract: The role of an innovative Pharmacist Independent Prescriber (PIP) for care homes to optimise medications has not been examined. We explored stakeholders' views on issues and barriers that the PIP might address to inform a service specification for the PIP intervention in older people's care homes. Focus groups ( n = 72 participants) and semi‐structured interviews ( n = 13) undertaken in 2015 across four sites in the United Kingdom captured the views of doctors, pharmacists, care‐home managers and staff, residents and relatives. Stakeholders identified their expectations of what service should be provided by PIPs, what might affect their support for the role, and barriers and enablers to providing the service. Transcripts were analysed using the Theoretical Domains Framework to identify key components, which were reviewed by stakeholders in 2016. A PIP service was envisaged offering benefits for residents, care homes and doctors but stakeholders raised challenges including agreement on areas where PIPs might prescribe, contextual barriers in chronic disease management, PIPs' knowledge of older people's medicine, and implementation barriers in integrated team‐working and ensuring role clarity. Introducing a PIP was welcomed in principle but conditional on: a clearly defined PIP role communicated to stakeholders; collaboration across doctors, PIPs and care‐home staff; dialogue about developing the service with residents and relatives, based on trust and effective communication. To embed a PIP service within increasingly complex care‐homes provision, the overarching theme from this research was that everyone must "understand each other's systems".